Comparison of forage productivity and its components of leaves and stems for some Atriplex’s species (Damascus University Journal of agriculture sciences, 2021)
The study was carried out on three pastoral plant species from the Chenopodiaceae family: Atriplex leucoclada Boiss., Atriplex halimus L. and Atriplex canescens (purch) Nutt. The aim of this research is to compare productivity and its components by leaf and stem of these species, as well as, these are most commonly used in rehabilitation programs for Arid and semi-arid Zones. This type of study helps to determine the contribution rates of the selected species in the botanic composition proposed, and therefore, the quantity and quality of forage productivity obtained in these areas. To achieve this, in the autumn (2018), five plants were selected and harvest at 50% level, for each of the species studied. The mass harvest was placed in paper bags identified by cards, to be dried in the laboratory, to determine the productivity and the ratio of leaf to stem.The results of the statistical analysis showed a significant difference (P≤0.05) between the species in their productivity, as well as the content of this mass from leaves and stems. Although the mass of both A. halimus and A. canescens was equal, the contribution of leaves in the mass produced by A. canescens was higher than that of A. halimus. It is known that the nutritive value of leaves was higher that of the stems in most plant species. The A. halimus showed a higher production than the A. leucoclada, but the ratio of leaves and stems appeared similar for both species
Keywords: Chenopodiaceae family; Atriplex; Forage productivity; Leaves to stems ratio